Socialization of Pamelo Cultivation Based on Biopesticides: a Community Service to Develop Organic Pamelo Tourism Village in Tambakmas Village, Sub-District Sukomoro, Magetan Sukomoro, Magetan Regency. - Sri Wiyatiningsih; Wiwik Sri Harijani; Wahyu Santoso; Riko Setya Wijaya (Nusantara Science and Technology Proceedings)
Community service, concerning the development of organic Pamelo Tourism Village based on biopesticides, has been carried out in Tambakmas Village, sub-district Sukomoro, Magetan Regency. Pamelo (Citrus maxima) has potential to be developed due to its ability to grow in tropical area and its raising production. Tambakmas Village in sub-district Sukomoro, Magetan, is one of the Pamelo production areas. Stem rot, caused by Botryodiplodia theobromae which is often happened to Pamelo trees in Tambakmas village, might reduce the quality and quantity of the harvest. However, the use of chemicals to prevent stem rot must be avoided to preserve the environment. Therefore, the development of Pamelo Organic Tourism Village requires biopesticide-based organic agriculture to restrain the disease. The socialization of biopesticide-based organic pamelo cultivation has been carried out to the Pamelo farmer group in Tambakmas Village from May to July 2019, it was integrated disease control including weeding, pruning, preparing and sterilizing the soil, and application of biopesticides. The severity of stem rot disease in Pamelo trees on the observation land with integrated disease control was examined and compared to the trees on the farmers' land without integrated disease control. Results of the observation land with integrated disease control showed that the disease severity slowly decreased by 16.20%. In contrast, disease severity that happened in the land without integrated disease control increased by 5.8%. Besides, the Pamelo trees that were treated with biopesticide developed a wound healing from the stem rot disease and exhibited growth of shoots on the treated region.